Effect of different anthropometry-driven block settings on sprint start performance - Neil Bezodis (European Journal of Sport Science, 2022)
Few studies have focused on the effect of individual anthropometrics when considering “set” position posture during the sprint start. This study aimed to measure the effect of different anthropometry-driven block settings on kinetic and kinematic parameters and performance during the start in well-trained and non-trained sprinters. Front block-starting line (FB/SL) distance was manipulated between 50% and 70% of each individual’s leg length at 5% intervals, whilst the inter-block distance was held constant at 45% of leg length. Thirty-six sprinters performed three maximal-effort 10 m sprints in each of the five conditions. Joint angles in the “set” position were quantified though 2D video analysis, the forces generated during block clearance phase were measured by dynamometric starting blocks, and times to 5 m and 10 m were measured with photocells. The effects of the five block setting conditions were largely consistent irrespective of ability level. Shorter FB/SL distances were associated with significantly more flexed hip and knee angles in the “set” position, a significantly more plantar flexed front ankle, and a significantly more dorsiflexed rear ankle. There were no significant effects of FB/SL distance on total block time, and thus the greater rear block peak forces and impulses produced from the shorter FB/SL distances combined with no effects on the resultant front block peak forces and impulses, led to higher levels of sprint start performance from the shorter FB/SL distances. Considering FB/SL distances closer to 50% of leg length may be beneficial for coaches and athletes to explore during sprint start training.